Multiple Image Fusion Using Laplacian Pyramid (International Journal of Engineering and Computer Science, 2014)
Image fusion is an important visualization technique of integrating coherent spatial and temporal information into a compact form. Laplacian fusion is a process that combines regions of images from different sources into a single fused image based on a salience selection rule for each region. In this paper, we proposed an algorithmic approach using a Laplacian and Gaussian pyramid to better localize the selection process. The input images are decomposed by using the Laplacian pyramid transformation. The final fused image can be obtained by using the inverse reconstruction of Laplacian pyramid transformation.